Study on the Growth of Falcataria moluccana at 14-Month-Old and the Productivity of Rice Plant (Oryza sativa) IPB 3S in Agroforestry System - Nurheni Wijayanto; Bagas Dipa Briliawan (Jurnal Sylva Lestari, 2022)
Agroforestry is a forestry and agriculture plant utilization system using sustainable land management to gain more products. Falcataria moluccana is a forestry plant that has been cultivated mostly in an agroforestry system by the Indonesian people, particularly on Java Island. Appropriate F. moluccana species selection and planting space in an agroforestry system are expected to improve plant growth and suppress the damage level that occurred in F. moluccana. The agroforestry system with F. moluccana and rice plant (Oryza sativa) is one of the alternative ways to support the national food needs. This study aimed to analyze the growth of various provenances of F. moluccana at the age of 14 months and analyze the productivity of IPB 3S rice in two planting spaces of F. moluccana. This study used a completely randomized two-factorial design, with the first factor being the provenance of F. moluccana, i.e., Solomon F1, Solomon F2, and local Kendal, and the F. moluccana spacing of 1.5 m x 3.0 m and 1.5 m x 1.5 m was the second factor. The F. moluccana growth parameters, rice plant growth parameters, and rice plant productivity in agroforestry systems were analyzed using an analysis of variance (ANOVA). If a significant effect on each parameter at a 5% confidence level occurred, the parameters were further analyzed with Duncan's Multiple Range Test (DMRT). The study found that provenance had no significant effect on the growth of 14-month-old F. moluccana. The results also showed that the growth of 14-month-old Solomon F2 had a relatively higher value on the parameters of height and diameter. The highest productivity of IPB 3S rice was found in the local F. moluccana shade at a spacing of 1.5 m x 1.5 m, reaching 0.201 tons/ha. The highest rice productivity was due to the magnitude of the light intensity received by rice of 5414.30 lux.